Manajemen Pembelajaran Berbasis Google Meet di SMA Negeri 7 Manado - Ayu Lestari; Herry Sumual; Viktory Nicodemus Joufree Rotty; Elni Jeini Usoh (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to find out in depth about: 1) Google Meet-based Learning Planning at SMA Negeri 7 Manado. 2) Implementation of learning based on google meet at SMA Negeri 7 Manado. 3) Google Meet-based Learning Evaluation at SMA Negeri 7 Manado. This type of research is field research, the approach used is a qualitative approach. The sources in this research data are primary data sources and secondary data sources. Data collection techniques are observation, interviews, documentation using inductive qualitative data analysis techniques. The results of the study show that: 1) Google meet-based learning planning at SMA Negeri 7 Manado is a subject teacher and arranges materials, media, and learning methods, namely preparing lesson plans, google meet links according to the subject matter. 2) Implementation of Google Meet-based learning at Manado 7 Public High School, namely the teacher delivering material, giving assignments and attendance through the Google Meet application. 3) Evaluation of Google Meet-based learning at Manado 7 Public High School, namely assignments are given via Google Meet and then sent back by students and after being assessed the assignment will be returned to the students again.